A high-performance readout circuit (ROIC) for VLWIR FPAs with novel current mode background suppression - Hao Li-chao; Ding Rui-jun; Zhang Jun-ling; Huang Ai-bo; Chen Hong-lei (2012 International Conference on Measurement, Information and Control, 2012)
This study designs a 32 × 32 readout integrated circuit (ROIC) for N-on-P very long wavelength (VLWIR) detectors. The new ROIC has the ability to operate with current mode background suppression in two steps, and increases the integration time and the signal-to-noise ratio (SNR) of image data. To improve the linearity and provide tight control of the detector bias, a buffered direct injection (BDI) unit cell is used as input circuit. By means of a sample and hold circuit, the infrared focal plane array (IRFPA) can be operated in snapshot mode and rolling mode. The simulation results confirm these advantages. With the 5.0 V power supply, the VLWIR ROIC provides the output dynamic range over 2.0 V and the well capacity more than 1 × 10 8 e - . The skimming error is less than 0.5%. The final chip will be fabricated with HHNEC 0.35 um 1P4M process technology, and the pixel occupies a 60 um × 60 um area. It can be operated at the temperatures of 50 K.